Funcionamiento familiar y autoestima en adolescentes de la institución educativa Pública san José - La Esperanza 2016 - Alvarez Villanueva, Katia Lizbeth (2017)
Research of type quantitative, descriptive and Correlational, had as objective determine the relationship that exists between the level of Family Functioning and the level of self-esteem in them teenagers of the institution educational public "San José"-La Esperanza. The sample was conformed by 128 students. The instruments used: scale of assessment of cohesion and adaptability family-PHASES III – Olson (1985) and inventory of self-esteem - Coopersmith (1989). The results are presented in statistical tables of one and double entry. Data analysis was applied to statistical test Chi square of independence of criteria. The following conclusions were obtained: With respect to family functioning, found a 28.9% at balanced level; 32.8%, In middle level and 38.3%, in extreme level; With regard to the level of self-esteem is found a 49.2% of adolescents with self-esteem very high; 17.2%, with self-esteem high; 18.7%, with self-esteem middle; 9.4%, with self esteem low and 5.5%, with self-esteem very low. Be found relationship between the working family and self-esteem (X2t = 220.2 p = 0.0059).